Distinct Neural Representation in the Dorsolateral, Dorsomedial, and Ventral Parts of the Striatum during Fixed- and Free-Choice Tasks - Ito, Makoto (J Neurosci, 2015)
The striatum is a major input site of the basal ganglia, which play an essential role in decision making. Previous studies have suggested that subareas of the striatum have distinct roles: the dorsolateral striatum (DLS) functions in habitual action, the dorsomedial striatum (DMS) in goal-directed actions, and the ventral striatum (VS) in motivation. To elucidate distinctive functions of subregions of the striatum in decision making, we systematically investigated information represented by phasically active neurons in DLS, DMS, and VS. Rats performed two types of choice tasks: fixed- and free-choice tasks. In both tasks, rats were required to perform nose poking to either the left or right hole after cue-tone presentation. A food pellet was delivered probabilistically depending on the presented cue and the selected action. The reward probability was fixed in fixed-choice task and varied in a block-wise manner in free-choice task. We found the following: (1) when rats began the tasks, a majority of VS neurons increased their firing rates and information regarding task type and state value was most strongly represented in VS; (2) during action selection, information of action and action values was most strongly represented in DMS; (3) action-command information (action representation before action selection) was stronger in the fixed-choice task than in the free-choice task in both DLS and DMS; and (4) action-command information was strongest in DLS, particularly when the same choice was repeated. We propose a hypothesis of hierarchical reinforcement learning in the basal ganglia to coherently explain these results.